Knowledge, attitudes, and practice toward sarcopenia among maintenance dialysis patients in Anhui, China - Qianyun Zhao; Xiyao Yang; Manzhen Bao; Miao Zhang; Deguang Wang (BMC Public Health)
Abstract Background To explore the knowledge, attitudes, and practice (KAP) toward sarcopenia among maintenance dialysis (MHD) patients in Anhui. Methods This multicenter cross-sectional study was conducted in November 2022 among MHD patients in the Anhui Province, China. A self-administered questionnaire was used to collect their demographic characteristics and KAP toward sarcopenia. Results A total of 1548 questionnaires were collected, with 909 (58.72%) being valid. The average knowledge, attitude, and practice scores were 4.45 ± 4.21 (possible range: 0–12), 28.21 ± 3.71 (possible range: 8–40), and 18.04 ± 4.28 (possible range: 7–35) points, respectively. The multivariable logistic regression showed that 5.1–10 years of dialysis (OR = 0.38, 95% CI: [0.15, 0.97]) and attitude scores (OR = 1.36, 95% CI: [1.25, 1.48]) were independently associated with practice. The structural equation model showed that knowledge had a direct effect on attitudes (β = 0.38, 95% CI: [0.33, 0.44]) and practice (β = 0.18, 95% CI: [0.11, 0.24]) and had an indirect effect on practice though attitudes (β = 0.42, 95% CI: [0.35, 0.50]). Conclusion The MHD patients in Anhui showed insufficient knowledge and moderate attitudes and practices toward sarcopenia. Proactive practice might be facilitated and achieved by improving knowledge and attitudes.